Virioplankton of the Kara Sea and the Yenisei River estuary in early spring. (5th February 2019) - Kopylov, Alexander I.; Sazhin, Andrey F.; Zabotkina, Elena A.; Romanenko, Anna V.; Romanova, Nadezda D.; Boltenkova, Мarina A.
Abstract: Here we present our research results on the virioplankton of the shelf zone of the Kara Sea. This is the first study of viruses and bacteria done in the Kara Sea in early spring when viruses can play an important role in the abundance and production control of the bacterioplankton. All other studies cover July–September, that is, when the Kara Sea is completely ice-free and the community of viruses and bacteria is in an absolutely different stage of development. The samples were collected and processed on board of the vessel "Norilskiy Nickel" (project Aker ACS 650) between March 29 and April 8, 2016 on the regular cruise Murmansk – Dudinka. The abundance of bacteria ( N B ) and viruses ( N V ) located both underneath the ice and in the open waters of the Kara Sea and the Yenisei River estuary varied within a range of (0.075–0.429) × 10 6 cells × ml −1 and (0.30–2.11) × 10 6 viral particles × ml −1, respectively, and the N V /N B ratio varied from 2.6 to 15.4. A positive correlation was found between N B and N V ( R = 0.70, p = 0.05). Viruses with capsid diameter of 16–297 nm were registered in the water samples examined. The transmission electron microscopy data show that the fraction of the virus-infected bacterial cells is about 0.2–2.3% of total N B . The mean viral-induced mortality of the bacteria calculated from all the sampling stations in the Kara Sea and the Yenisei River estuary was 7.8 ± 1.2% (with a range from 1.4 to 20.2%) of the daily bacterioplankton production. Our results show that viruses play an important role in the abundance and production of bacterioplankton control in early spring.